Implementation of a compatibility assessment of the engagement system and the employee motivational profile in company human resources management - Pritvorova, T.P.; Tasbulatova, B.K.; Slinkova, O.K. (BUKETOV BUSINESS REVIEW, 2020)
Object: The object of this study is to develop and test a method for assessing the conformity of a system of an employee’s engagement in a company and his motivation profile. Methods: We have applied methods of sociological survey of company staff and subsequently, performed graphical and statistical analysis of the achieved results (an index method). We also used the matrix method for assessing the identified risks of employee dissatisfaction. Findings: The results of the study confirm the effectiveness of the index method we propose. It allows conducting regular screening among company staff to identify risk factors for the formation of the employee’s “dissatisfaction,” which in the future may get him fired or burn out. This shall allow diagnosing the issue of discrepancies between motivation of the subject and measures for engagement used by the employer. In addition to the index, the authors have developed a risk assessment matrix based on a combination of significance of the factor (and its sub-factors) for the employee and probability (possibility) of the employee’s influence on this sub-factor. Conclusions: The application of the proposed two-stage assessment method shall allow the personnel department to timely diagnose the issue of inconsistencies in the motivational profile and the applied engagement measures for each employee and develop proposals for improving it.